In Vivo Biotransformation Rates of Organic Chemicals in Fish: Relationship with Bioconcentration and Biomagnification Factors - Lo, Justin C; Letinski, Daniel J; Parkerton, Thomas F; Campbell, Dave A; Gobas, Frank A. P. C (Environmental science & technology, 2016)
In vivo dietary bioaccumulation experiments for 85 hydrophobic organic substances were conducted to derive the in vivo gastrointestinal biotransformation rates, somatic biotransformation rates, bioconcentration factors (BCF), and biomagnification factors (BMF) for improving methods for bioaccumulation assessment and to develop an in vivo biotransformation rate database for QSAR development and in vitro to in vivo biotransformation rate extrapolation. The capacity of chemicals to be biotransformed in fish was found to be highly dependent on the route of exposure. Somatic biotransformation was the dominant pathway for most chemicals absorbed via the respiratory route. Intestinal biotransformation was the dominant metabolic pathway for most chemicals absorbed via the diet. For substances not biotransformed or transformed exclusively in the body of the fish, the BCF and BMF appeared to be closely correlated. For substances subject to intestinal biotransformation, the same correlation did not apply. We conclude that intestinal biotransformation and bioavailability in water can modulate the relationship between the BCF and BMF. This study also supports a fairly simple rule of thumb that may be useful in the interpretation of dietary bioaccumulation tests; i.e., chemicals with a BMFL of <1 tend to exhibit BCFs based on either the freely dissolved (BCFWW,fd) or the total concentration (BCFWW,t) of the chemical in the water that is less than 5000.